Serum adiponectin and resistin levels in de novo and relapsed acute lymphoblastic leukemia children patients. - Hatim A El-Baz; Tamer E Mosa; Elham M Elabd; Amal Ramadan; Ahmed S Elharoun; Elsayed A Elmorsy; Manal I Fouda (Tehran University of Medical Sciences, 2013)
Adipose tissue secretes a large number of adipocytokines such as leptin, resistin, and adiponectin. Many of these hormones and cytokines are altered in obese individuals and may lead to disruption of the normal balance between cell proliferation, differentiation, and apoptosis. The aim of our work was to investigate the disturbance of secretion of adiponectin and resistin in de novo and relapsed acute lymphoblastic leukemia (ALL) in Egyptian children and determine whether adiponectin and resistin are implicated in increased risk relapse compared to healthy individuals.Measurements of adiponectin and resistin were performed at diagnosis, in 32 patients with de novo ALL aged 3 to 18 years (mean 9.8 y) and 19 children with relapsed ALL aged 5 to 17 (mean 9.9 yr). 10 apparently healthy children with matched age and sex were used as controls.Mean adiponectin levels were low (P < 0.05), whereas mean resistin levels were high (P